2017
DOI: 10.7150/ijms.18127
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Reconstruction with Human Amniotic Membrane in a Xenograft Rat Model: A Preclinical Study

Abstract: Background: Human amniotic membranes (HAMs) are assumed to have a number of unique characteristics including durability, hypoallergenic and anti-inflammatory properties.Materials and Methods: Multilayer HAMs from caesarian sections were applied to repair defined bladder defects in male Sprague-Dawley rats. The animals were sacrificed at 7, 21 and 42 days after implantation. Bladder volume capacity after grafting was measured. Histological analyses were performed to asses a number of parameters including HAM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
0
31
0
1
Order By: Relevance
“…Previously we have shown that hAM as a scaffold enables the development of tissue-engineered urothelium, which is in molecular and ultrastructural properties comparable to native urothelium (Jerman et al, 2014). Other studies have already used the hAM for bladder (Shakeri et al, 2008;Adamowicz et al, 2016;Barski et al, 2017) and urethral reconstruction (Shakeri et al, 2009;Wang et al, 2014) in animal models. Moreover, hAM was also used for reconstructive surgery of the ureteral obstruction in patients with extensive ureteral strictures (Koziak et al, 2007) and reconstructive surgery of strictured urethra (Koziak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have shown that hAM as a scaffold enables the development of tissue-engineered urothelium, which is in molecular and ultrastructural properties comparable to native urothelium (Jerman et al, 2014). Other studies have already used the hAM for bladder (Shakeri et al, 2008;Adamowicz et al, 2016;Barski et al, 2017) and urethral reconstruction (Shakeri et al, 2009;Wang et al, 2014) in animal models. Moreover, hAM was also used for reconstructive surgery of the ureteral obstruction in patients with extensive ureteral strictures (Koziak et al, 2007) and reconstructive surgery of strictured urethra (Koziak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on animals and humans showed good results in terms of urothelial re-epithelialization, but with an inadequate muscle regeneration because it was incomplete, disorganized, not well integrated into the new wall, and without adequate vascularization or innervation [ 7 ]. This fact determines the final bladder functionality [ 24 , 26 ]. Some studies have even performed a specific mechanical analysis to study the tensile strength of the new wall [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semiquantitative scores of lymphocytes from 0 to 3 were used for inflammation. Inflammation of the ulcerated region was scored by counting lymphocytes in three fields (200× magnification) in three observer-randomized H&E slides (semiquantitative score: 0, < 5% cells/field; 1, 5–25%; 2, 25–50%; 3, > 50%) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%